Disparate trends of atherosclerotic plaque evolution in stroke patients under 18-month follow-up: a 3D whole-brain magnetic resonance vessel wall imaging study. Issue 1 (February 2022) - Xiao, Jiayu; Song, Shlee S; Schlick, Konrad H; Xia, Shuang; Jiang, Tao; Han, Tong; Jackson, Robert J; Diniz, Marcio A; Dumitrascu, Oana M; Maya, Marcel M; Lyden, Patrick D; Li, Debiao; et al.
Purpose: The trend of atherosclerotic plaque feature evolution is unclear in stroke patients with and without recurrence. We aimed to use three-dimensional whole-brain magnetic resonance vessel wall imaging to quantify the morphological changes of causative lesions during medical therapy in patients with symptomatic intracranial atherosclerotic disease. Methods: Patients with acute ischemic stroke attributed to intracranial atherosclerotic disease were retrospectively enrolled if they underwent both baseline and follow-up magnetic resonance vessel wall imaging. The morphological features of the causative plaque, including plaque volume, peak normalized wall index, maximum wall thickness, degree of stenosis, pre-contrast plaque-wall contrast ratio, and post-contrast plaque enhancement ratio, were quantified and compared between the non-recurrent and recurrent groups (defined as the recurrence of a vascular event within 18 months of stroke). Results: Twenty-nine patients were included in the final analysis. No significant differences were found in plaque features in the baseline scan between the non-recurrent ( n = 22) and recurrent groups ( n = 7). The changes in maximum wall thickness (–13.32% vs. 8.93%, P = 0.026), plaque-wall contrast ratio (–0.82% vs. 3.42%, P = 0.005) and plaque enhancement ratio (–11.03% vs. 9.75%, P = 0.019) were significantly different between the non-recurrent and recurrent groups. Univariable logistic regression showed that the increase in plaque-wall contrast ratio (odds ratio 3.22, 95% confidence interval 1.55–9.98, P = 0.003) was related to stroke recurrence. Conclusion: Morphological changes of plaque features on magnetic resonance vessel wall imaging demonstrated distinct trends in symptomatic intracranial atherosclerotic disease patients with and without stroke recurrence.